Dynamics in complex systems amidst crisis 2008+: Financial regulatory and supervisory reflections - Piotr Łasak; Sławomir Wyciślak (Risks, 2022)
Every financial crisis triggers some regulatory and supervisory changes related to the ensuing threats. These regulations usually address specific types of risks and reduce them but do not protect the entire system from another crisis. The aim of this study was to develop a conceptual framework of financial system resilience based on the theoretical approach of complex system theory and its explanation of these systems' self-adaptation. Our analysis embraces the time since the 2008+ financial crisis in the United States. We argue that the digitalization of financial markets may contribute to the greater safety of the banking sector. We adopted blockchain technology for the pattern of self-modification mechanisms of the financial system. The main findings highlight that the blockchain technology incorporated into the system approach and applied to financial regulation and supervision can significantly improve the safety of the financial markets.
Keywords: 330; bank crisis; blockchain technology; complex system theory; financial markets regulatio; financial markets supervision